Strengthening Micro-Entrepreneur Capacity Through Community Economic Assistance Programs An Evaluation of Participatory Development Practices - Agus Setianto; Wargo; Wardani (Zabags International Journal of Engagement, 2026)
Micro-enterprises play a strategic role in generating employment and improving community welfare, yet they continue to face limitations in managerial capacity, access to capital, technological adoption, and marketing networks. This study aims to analyze the implementation of community economic assistance programs in strengthening micro-entrepreneur capacity through participatory development practices, while evaluating their contribution to managerial, production, marketing, and business development aspects. Employing a qualitative evaluative-descriptive approach, data were collected through observation, in-depth interviews, and documentation, and analyzed using data condensation, data display, and conclusion drawing with triangulation verification. The findings reveal that active involvement of micro-entrepreneurs in planning, implementation, and evaluation stages enhances ownership, independence, and adaptability to economic challenges. Technical and managerial mentoring strengthens production capacity and resource management, while social capital expands business networks and digital technology integration supports market adaptation. The contribution of this study lies in developing a conceptual framework that integrates community empowerment, participatory development, capacity building, social capital, and micro-entrepreneurship theories. It also provides a practical evaluation model for policymakers, non-governmental organizations, and economic empowerment institutions to design more effective and sustainable assistance programs.